Wybór Ambrożego Aureliusza na biskupa Mediolanu: cud, czy celowe działanie Walentyniana I? - Spychała, Dariusz (Studia Europaea Gnesnensia, 2014)
Aurelius Ambrosius is a characteristic example of an official of the imperial administration who made a clerical career in the early days of Christianization of the Empire. His life was full of unexpected events. Born into a Christian family, he still put off the moment of baptism – a common custom, yet not recommended by the Church. His stable career path changed radically when Ambrosius was elevated to the rank of Bishop of Milan.